Hubungan Kepatuhan Cuci Tangan terhadap Kejadian Demam Typoid pada Anak di RSU PKU Muhammadiyah Delanggu - Sarifah Kumalha; Nurul Istiqomah; Munaaya Fitriyya (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Typhoid fever is an acute infectious disease caused by Salmonella typhi bacteria, and is generally spread through contaminated food or drinks. One of the effective prevention efforts is to maintain personal hygiene, especially washing your hands before eating. This study aims to determine the relationship between handwashing compliance with the incidence of typhoid fever in children treated at PKU Muhammadiyah Delanggu Hospital. The research design used is observational analysis with a quantitative approach. The sampling technique was carried out by accidental sampling with a total of 34 children. Data were collected through questionnaires that measured the level of handwashing compliance and the history of typhoid fever incidence. The analysis of the relationship between variables was carried out using the Chi Square statistical test. The results showed that as many as 20 children (58.82%) had good handwashing compliance, with an average compliance score of 7.79 ± 1.666. Meanwhile, as many as 18 children (52.94%) were recorded to have typhoid fever. The results of the Chi Square test showed a p-value of 0.681, which means that there was no significant association between handwashing compliance and the incidence of typhoid fever in children at the study site. The conclusion of this study is that handwashing compliance has not shown a significant relationship with the incidence of typhoid fever in children at PKU Muhammadiyah Delanggu Hospital. These findings indicate the need for further studies by considering other factors such as water quality, environmental sanitation, and food consumption habits, in order to gain a more comprehensive understanding of the prevention of typhoid fever in children.